2019
DOI: 10.1155/2019/5052185
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Dynamics Based Optimal Fuzzy Controller for a Robot Manipulator via Particle Swarm Optimization

Abstract: This paper endeavors to contribute to the field of optimal control via presenting an optimal fuzzy Proportional Derivative (PD) controller for a RPP (Revolute-Prismatic-Prismatic) robot manipulator based on particle swarm optimization and inverse dynamics. The Denavit-Hartenberg approach and the Jacobi method for each of the arms of the robot are employed in order to gain the kinematic equations of the manipulator. Furthermore, the Lagrange method is utilized to obtain the dynamic equations of motion. Hence, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The constrains is included in the singularities block implies the difference between the real tuple position and the reference tuple should not exceed 0.6. The Homogeneous Transformation Matrix is obtained according to [23,24] is shown in (11).…”
Section: Kinenamatic Robotmentioning
confidence: 99%
“…The constrains is included in the singularities block implies the difference between the real tuple position and the reference tuple should not exceed 0.6. The Homogeneous Transformation Matrix is obtained according to [23,24] is shown in (11).…”
Section: Kinenamatic Robotmentioning
confidence: 99%
“…When the right foot is moving, the transformation matrix will proceed from the world coordinate frame to the left foot and vice-versa. Mahmoodabadi & Ziaei (2019) proposed a DH approach and Jacobi method for each of the arms of a robot in order to gain the kinematic equations of the manipulator. Furthermore, the Lagrange method was utilized to obtain the dynamic equations of motion.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, the effectiveness of FLC can be improved if the dynamic modeling is incorporated. For example, in [7], inverse dynamics were used in a fuzzy-model-based adaptive robust controller for the tracking control of a parallel manipulator and for reducing the chattering, and in [8], a dynamics-based optimal fuzzy controller for a robot manipulator via particle swarm optimization was inspected. It was found that the fuzzy controller based on inverse dynamics provides a near-zero steady state error.…”
Section: Introductionmentioning
confidence: 99%